THE USE OF AUTHENTIC MATERIALS IN CLASSROOMS - Nafosat Ilkhomova (Journal of new century innovations, 2022)
Abstract: The sources of authentic materials that can be used in the classroom are infinite, but the most common are newspapers, magazines, TV programs, movies, songs and literature. One of the most useful is the Internet. Whereas newspapers and any other printed material date very quickly, the Internet is continuously updated, more visually stimulating as well as being interactive, therefore promoting a more active approach to reading rather than a passive one.